Quality of Differentiated Indonesian Language Learning Process at Vocational High Schools in the Digital Era - Hasnah Setiani; Ida Zulaeha; Deby Luriawati Naryatmojo (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Learning differentiate aims to make it happen public Study own ability digitalization, thinking critical, communicative, as well collaborative in accordance with need social society 21st century. Implementation on the eyes lesson Indonesian is established​ as foundation from ability literacy ( language And thinking ) addressed For communicate in social public. Learning differentiate eye lesson Indonesian on​ level School Intermediate Vocational implemented as deep strategy education For realize objective education, competence graduates, and prepare society face challenge life 21st century and the digital era. Research is conducted to analyze and describe quality learning process differentiated Indonesian​ on School Intermediate Vocational. Approach to research This is evaluative with method quantitative descriptive And qualitative. Population And research sample, namely class X Desain Komunikasi Visual 1 at SMK Negeri 11 Semarang, class X Boga 2 at SMK Negeri 6 Semarang, and class X Accounting 3 at SMK Negeri 9 Semarang. Source of research data that is interview with Waka Curriculum , Educators, participants educate, observe, and documentation. Technique data analysis using Miles and interactive models Huberman And technique scoring rating scale . Results of research on the quality of the differentiated Indonesian language learning process at SMK N 6 Semarang, SMK N 9 Semarang, and SMK N 11 Semarang occupied the good category with an average score of 75%. The learning process in each educational unit has met the indicators of (1) learning planning, (2) learning implementation, and (3) good learning assessment.